2024
DOI: 10.1039/d4ob00343h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-promoted regioselective hydrocarboxylation of allenes with formate salt and CO2

Xian-Ming Zhang,
Bao-En Liu,
Zhen-Qiang Zhang
et al.

Abstract: Visible-light-promoted hydrocarboxylation of allenes with formate salt and CO2 was developed for the first time using commercially available [Ir(ppy)2(dtbbpy)]PF6 as photocatalyst. This strategy provides an efficient and practical method to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…To circumvent some drawbacks associated with CO gas, efforts have also been made for the development of hydrocarboxylation with nongaseous CO surrogates . For example, we and others , have shown that hydrocarboxylation can be achieved with HCO 2 H under mild conditions assisted with HCO 2 Ar or Ac 2 O. , Readily available oxalic acid could also serve as a potential carbonyl source for the hydrocarboxylation of olefins with a possible distinct reaction mechanism, which could provide new opportunities to regulate the reactivity and selectivity. The hydrocarboxylation of olefins with oxalic acid in the presence of additional CO has been reported …”
mentioning
confidence: 99%
“…To circumvent some drawbacks associated with CO gas, efforts have also been made for the development of hydrocarboxylation with nongaseous CO surrogates . For example, we and others , have shown that hydrocarboxylation can be achieved with HCO 2 H under mild conditions assisted with HCO 2 Ar or Ac 2 O. , Readily available oxalic acid could also serve as a potential carbonyl source for the hydrocarboxylation of olefins with a possible distinct reaction mechanism, which could provide new opportunities to regulate the reactivity and selectivity. The hydrocarboxylation of olefins with oxalic acid in the presence of additional CO has been reported …”
mentioning
confidence: 99%